Perception of basic emotions in music: Culture-specific or multicultural? - Argstatter, Heike (Psychology of music, 2016)
The perception of basic emotions such as happy/sad seems to be a human invariant and as such detached from musical experience. On the other hand, there is evidence for cultural specificity: recognition of emotional cues is enhanced if the stimuli and the participants stem from the same culture. A cross-cultural study investigated the following research questions: (1) How are six basic universal emotions (happiness, sadness, fear, disgust, anger, surprise) perceivable in music unknown to listeners with different cultural backgrounds?; and (2) Which particular aspects of musical emotions show similarities and differences across cultural boundaries? In a cross-cultural study, 18 musical segments, representing six basic emotions (happiness, sadness, fear, disgust, anger, surprise) were presented to subjects from Western Europe (Germany and Norway) and Asia (South Korea and Indonesia). Results give evidence for a pan-cultural emotional sentience in music. However, there were distinct cultural, emotion and item-specific differences in emotion recognition. The results are qualified by the outcome measurement procedure since emotional category labels are language-based and reinforce cultural diversity.